Asset Recovery in Contemporary Islamic Law: Reconstructing Public Wealth Protection through Maqāṣid al-Sharīʿah - Ahyar Gayo; Evi Djuniarti; Syprianus Aristeus; Diana Yusyanti; Marulak Pardede; Yakub Abdulwaheed Olareweju (MILRev: Metro Islamic Law Review, 2026)
Persistent corruption and the limited recovery of state losses expose significant weaknesses in contemporary asset recovery mechanisms. Although anti-corruption laws provide instruments for confiscation and compensation, recovered illicit assets remain substantially below the financial losses caused by corruption. This study analyses the effectiveness of asset recovery in Indonesia and reconstructs a framework for protecting public wealth from the perspective of maqāṣid al-sharīʿah. It employs normative legal research using statutory, conceptual, and maqāṣid-based approaches. Primary legal materials comprise anti-corruption and anti-money laundering legislation, judicial decisions, and relevant international instruments; secondary materials include scholarship on asset recovery, corruption, and Islamic legal theory. The materials are analysed through doctrinal interpretation and maqāṣid-based evaluation. The findings show that Indonesia's asset recovery regime remains predominantly conviction-based and is constrained by difficulties in asset tracing, weak enforcement of compensation orders, fragmented regulation, and barriers to recovering assets transferred to third parties or foreign jurisdictions. From a maqāṣid perspective, corruption violates ḥifẓ al-māl by diverting public resources from their social functions and undermining collective welfare. Asset recovery should therefore be understood not merely as punishment but as a means of restoring public rights, protecting collective wealth, and advancing distributive justice. The article proposes a maqāṣid-based framework that prioritises the protection of public wealth, strengthens asset-centred forfeiture mechanisms, and aligns anti-corruption governance with the objectives of Islamic law.